2017
DOI: 10.1007/s40519-017-0378-9
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorders and food addiction in men with heroin use disorder: a controlled study

Abstract: Co-occurring binge eating disorder and food addiction are highly frequent in men with heroin use disorder. Screening for binge eating disorder and food addiction in patients with substance use disorder is important, as interventions may improve treatment outcome in this patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…In a cross-sectional assessment of diet quality in individuals with a lifetime history of attempted suicide, researchers found that fruits, vegetables and meat were significantly under-consumed in adults who had ever attempted suicide [ 19 ]. In a controlled study of eating disorders and food addiction in men with heroin use disorder in Turkey, food addiction was found associated with having a history of suicide attempts [ 20 ]. In a study of the association of eating habits and suicide attempts in psychiatric patients in Mexico, a history of suicide attempts was associated with consumption of pork and other types of meat [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional assessment of diet quality in individuals with a lifetime history of attempted suicide, researchers found that fruits, vegetables and meat were significantly under-consumed in adults who had ever attempted suicide [ 19 ]. In a controlled study of eating disorders and food addiction in men with heroin use disorder in Turkey, food addiction was found associated with having a history of suicide attempts [ 20 ]. In a study of the association of eating habits and suicide attempts in psychiatric patients in Mexico, a history of suicide attempts was associated with consumption of pork and other types of meat [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a sample of Dutch adolescents ( n = 2653), symptoms of FA were positively associated with alcohol use, cannabis use, smoking, and sugar intake [ 8 ]. Men with heroin use disorder ( n = 100) had triple the odds of meeting criteria for BED or FA compared to controls [ 70 ]. Not surprisingly, FA diagnosis was associated with more severe craving.…”
Section: Substance Use Disordersmentioning
confidence: 99%
“…Conclusions suggest giving more consideration to the impact of highly palatable foods for some people seeking ED treatment. A few studies have linked FA and SUD ( 264 , 265 ) but additional research should be conducted on individuals with SUD in order to further understand how eating behaviors can progress throughout the recovery process. Interaction effects between FA, SUD, and ED have not yet been adequately described.…”
Section: Food Addiction and Eating Disordersmentioning
confidence: 99%